Scholarly podcasting why, what, how? - Cook, Ian M. (Routledge, 2023)
"Exploring what academic podcasting is and what it could be, this book is the first to consider the why, what, and how academics engage with this insurgent, curious craft. Featuring interviews with 101 podcasting academics, including scholars and teachers of podcasting, this book explores the motivations of scholarly podcasters, interrogates what podcasting does to academic knowledge, and leads potential podcasters through the creation process from beginning to end. With scholarship often trapped inside expensive journals, wrapped in opaque language, and laced with a standoffish tone, this book analyses the implications of moving towards a more open and accessible form. This book will also inform, inspire, and equip scholars of any discipline, rank, or affiliation who are considering making a podcast or who make podcasts with the background knowledge and technical and conceptual skills needed to produce high-quality podcasts through a reflexive critique of current practices"--Provided by publisher.